IMPLEMENTASI PERATURAN DAERAH KOTA PEKANBARU NOMOR 11 TAHUN 2001 TENTANG PENATAAN DAN PEMBINAAN PEDAGANG KAKI LIMA DI PASAR PEMERINTAH KOTA PEKANBARU - Reno Efaldi; Muhammad Ridwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
One that wills be observational deep study this time is Cik Puan's market that lies to be cleared a root by Jack Fruit that is now shift name as my Gentleman road Tambusai. This traditional market categorised market which adequately clamorous with cloister business man existence. This market even also market which adequately frequent being announced at term media dailies cities. Besides, this traditional market its position is at Pekanbaru's down town and lies in the middle protocol golden mean that do ever multitude passed through by Pekanbaru's city society.Until currently is still get we meet business man that still selling until tumpah ruah at along my gentleman road tambusai that. This indeed all beget jam that does ever become routine who shall face Pekanbaru's city society while wants by the way of that. All this time government has provided building and facility that reasonably to them selling those are built in Cik Puan's Market region that. But until now haven't available consciousness on their behalf to want move or direlokasi to place already being provided previous. Eventually if they all have the honour direlokasi, this will make one new landscape which padagang this cloister gets selling with every consideration, dainty, apple-pie order and slalu becomes clear market.To the effect of observational it is To know factor that regard Region regulation performing Pekanbaru's City Number 11 Years 2001 about Settlement and Cloister Business Man Constructions at Cities Commanding Market Pekanbaru and effort that is done in render Region regulation performing Pekanbaru's City Number 11 Years 2001 about Settlement and Cloister Business Man Constructions at Cities Commanding Market Pekanbaru.Type and research method that is utilized is Descriptive observational type, one that diartikan as process of trouble-shooting that at investigates by explain or describe subjek's situation and also research object on present moment bases observable fact or as it were marks sense. In writer data collecting do visceral interview and penelusuran a variety document and archives on duty.Result observationaling to point out that there are some factor which regard Region regulation performing Pekanbaru's City Number 11 Years 2001 about Settlement and Cloister Business Man Constructions which is marks sense Communication Factor, Resource, Disposition and Bureaucracy that regards direct role and government in going penegakan Region regulation. On duty Market interrupts me on duty in charge manage Cloister business man problem have done good collaboration with the other institution that can help penegakan this region regulation. On duty Market gets main coordination with Satuan Pamong Praja's Police in penertibannya helped by police force Party participation in the act security which its following most operations deep net workaday that is done in meminimalisir cloister business man at this Pekanbaru's City.Keyword: Implementation, Settlement and Cloister Business Man Construction, Communication factor, Resource, Disposition and Bureaucracy